Tindak tutur ekspresif dalam novel episode hujan karya: Lucia Priandarini - Aulia, Astri Rahmah; Siregar, Asrul; Kudadiri, Amhar (Aksara: Jurnal Bahasa dan Sastra, 2024)
The discussion in this research is about expressive speech acts with a pragmatic review. The aim of this research was to find out how many forms and functions of expressive speech acts. The data source used is the Novel Rain Episode by Lucia Priandarini. This research uses qualitative descriptive research. The data collection stage of the research used researchers using data collection techniques contained in quotations from sentences in the novel Episode Rain to obtain a number of data. The theory used is John Searle's speech act theory. The form of speech acts uses Wijana's theory. The function of speech acts using John Searle's theory is classified into expressive speech act functions including The function of apologizing, complaining, getting angry, criticizing, thanking, and congratulating. The benefit of this research is to provide additional knowledge and understanding of expressive speech acts which are studied using pragmatics. The results of this research show several forms of expressive speech, including apologizing speech (7), complaining expressive speech (2), angry expressive speech (5), criticizing expressive speech (1), congratulating expressive speech (1), expressive speech of thanks (1). Meanwhile, the function of expressive speech in the novel consists of several functions including: The function of apologizing (7), complaining (2), getting angry (5), criticizing (1), congratulating (1), and thanking (1).Keywords: Pragmatics, Expressive Speech Acts, Function, Form